Leucemia-Linfoma Linfoblástico de Células Precursoras B con eosinofilia severa, en una paciente adulta joven - Tello Vera, Stalin (2020)
Introduction: Acute lymphoblastic leukemia (ALL) of B (1,2) cells, is the most common subtype of ALL in children. ALL that presents as hypereosinophilia in peripheral (3) blood, is very rare and the incidence is <1%. Case Report: In this case, is presented a girl, 25 year old girl, initially diagnosed as community acquired pneumonia and leukemoid reaction with hypereosinophilia. Wich subsequently re-enters with respiratory distress, also finding double moderate mitral injury, moderate tricuspid insufficiency, mild pulmonary hypertension and mild pericardium effusion; finally, a definitive diagnosis of acute lymphoblastic leukemia B with the help of auxiliary examinations.